UNLOCKING THE FUTURE OF ASSET MANAGEMENT: A SYSTEMATIC REVIEW OF IOT TRENDS, CHALLENGES, AND OPPORTUNITIES - Sari, Yeni Priatna; Afriliana, Ida; Almasyhari, Abdul Kharis; Nurkhasanah, Ayu (Universitas Mercu Buana Yogyakarta, 2025)
This study aims to systematically review various literature that discusses the use of the Internet of Things (IoT) in asset management. IoT, as one of the rapidly developing technologies, has significant potential in supporting the automation and efficiency of accounting processes. The study identifies the latest trends in IoT adoption, both from the corporate and regulatory side.This study will review research with the limitations of research published by Scopus indexed research and research conducted over the last 10 years. Keywords that will be used to search for various literature include the internet of things, asset information system.The findings of this literature review will provide a foundation for researchers and accounting practitioners to develop more innovative and responsive accounting systems to the evolving needs of businesses in the digital era as well as research that can be developed related to technology and asset management.